A Recurrent Pathogenic Variant of INPP5K Underlies Autosomal Recessive Congenital Muscular Dystrophy With Cataracts and Intellectual Disability: Evidence for a Founder Effect in Southern Italy - D’Amico, Adele; Fattori, Fabiana; Nicita, Francesco; Barresi, Sabina; Tasca, Giorgio; Verardo, Margherita; Pizzi, Simone; Moroni, Isabella; De Mitri, Francesca; Frongia, Annalia; Pane, Marika; Mercuri, Eugenio; et al. (Frontiers in Genetics, 2020)
Inositol polyphosphate-5-phosphatase K (INPP5K [MIM: 607875]) acts as a PIP3 5-phosphatase and regulates actin cytoskeleton, insulin and cell migration. Biallelic pathogenic variants in INPP5K have recently been reported in patients affected by a form of muscular dystrophy with childhood-onset. Affected patients have limb girdle muscle weakness, often associated with bilateral cataracts, short stature, and intellectual disability. Here we report four patients affected by INPP5K-related muscle dystrophy, who were apparently unrelated but originated from the same geographical area in South Italy. These patients manifest a recognizable phenotype characterized by early onset muscular dystrophy associated to short stature and intellectual disability. All affected subjects were homozygous or compound heterozygous for the c.67G>A (p.Val23Met) missense change and shared a common haplotype, indicating the occurrence of a founder effect.